2019
DOI: 10.1039/c8gc03075h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic transfer hydrogenation of oleic acid to octadecanol over magnetic recoverable cobalt catalysts

Abstract: Earth-abundant magnetic cobalt is highly efficient for CTH of oleic acid with isopropanol as a hydrogen donor, affording 100% conversion as well as 91.9% octadecanol yield at 200 °C, which can be ascribed to the synergistic effect between Coδ+ and Co0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The Lewis acid sites activated the carbonyl groups of LA, while the base sites were beneficial for the dissociation of hydroxyl groups in 2-propanol to form the active H adatom . The unsaturated carbonyl compounds are apt to bond strongly to metallic sites and interact with the adjacent adsorbed H species for hydrogenation. ,, The M–H + adducts could be formed, promoting the dehydrogenation of alcohols . Moreover, the acidic and basic sites could also enhance the esterification/lactonization reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Lewis acid sites activated the carbonyl groups of LA, while the base sites were beneficial for the dissociation of hydroxyl groups in 2-propanol to form the active H adatom . The unsaturated carbonyl compounds are apt to bond strongly to metallic sites and interact with the adjacent adsorbed H species for hydrogenation. ,, The M–H + adducts could be formed, promoting the dehydrogenation of alcohols . Moreover, the acidic and basic sites could also enhance the esterification/lactonization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…51 The unsaturated carbonyl compounds are apt to bond strongly to metallic sites and interact with the adjacent adsorbed H species for hydrogenation. 23,52,53 The M−H + adducts could be formed, promoting the dehydrogenation of alcohols. 54 Moreover, the acidic and basic sites could also enhance the esterification/ lactonization reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explain these results, we consider that the most active sites for the slow steps of SDO are situated on the surface of Co 0 and the interfaces of Co 0 /CoO where sites with moderate acidity are also developed (NH 3 -TPD results). In this regard, Wang et al 45 identified synergy between Co 0 and Co δ+ species in hydrodeoxygenation reactions. Chen et al 46 proposed the development of active sites at the interfaces between Co 0 and CoO x species being responsible for higher alcohol synthesis from syngas.…”
Section: Methodsmentioning
confidence: 99%
“…Nano catalysts have attracted much attention owing to their high efficiency as well as the green features of the reaction processes free of ligands or additives . In field applications, magnetic materials, such as Fe 3 O 4 , have been widely used as the support for catalytic metal nanoparticles (NPs) to achieve convenient magnetic separation as they enable more efficient catalyst recovery process, compared with the traditional homogeneous or heterogeneous catalysts . However, aggregation of active metal NPs may result in catalyst deactivation and is a major issue hindering their industrial application.…”
Section: Introductionmentioning
confidence: 99%